2016
DOI: 10.3390/s16050748
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Distributed Optical Fiber Sensors for Civil Engineering Applications

Abstract: The application of structural health monitoring (SHM) systems to civil engineering structures has been a developing studied and practiced topic, that has allowed for a better understanding of structures’ conditions and increasingly lead to a more cost-effective management of those infrastructures. In this field, the use of fiber optic sensors has been studied, discussed and practiced with encouraging results. The possibility of understanding and monitor the distributed behavior of extensive stretches of critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
315
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 641 publications
(348 citation statements)
references
References 125 publications
(167 reference statements)
1
315
0
3
Order By: Relevance
“…Distributed optical fiber sensing using Rayleigh-based phase sensitive optical time-domain reflectometry (φOTDR) is gaining a great deal of interest in areas such as structure health monitoring, aerospace or material processing [1,2]. φOTDR-based sensors are routinely employed for the monitoring of mechanical variations (e.g., vibrations, displacements, etc.)…”
mentioning
confidence: 99%
“…Distributed optical fiber sensing using Rayleigh-based phase sensitive optical time-domain reflectometry (φOTDR) is gaining a great deal of interest in areas such as structure health monitoring, aerospace or material processing [1,2]. φOTDR-based sensors are routinely employed for the monitoring of mechanical variations (e.g., vibrations, displacements, etc.)…”
mentioning
confidence: 99%
“…The strain precisions are OFDR (1 με), BOTDR (40 με), BOTDA (20 με), BOFDA (2 με), BOCDA (10 με), FBG (1 με). The OFDR is a type of DOFS technologies which has shorter measuring time, higher sensitivity, and higher spatial resolution than other frequently-used DOFS technologies like BOTDR, BOTDA, BOFDA, BOCDA, and so on [10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The principle is to transform photon energy into electric field and current by means of semiconductor with specific structure, and its quantum efficiency is 80~90%. Barrias, A. et al [6] found that the singular area of internal temperature in buildings would not be detected inevitably because of a large layout spacing of thermistor thermometers and other reasons. Fiber optic sensing is developed with the development of optical communication and the development of IT industry.…”
Section: State Of the Artmentioning
confidence: 99%
“…After fitting the sensing data of 2 sliding optical fibers, we can draw a conclusion that the coefficient & 1 and & 2 are close to each other. We can get the data fitting of & 1 and & 2 in pairs using formula (6) in several groups of experiments, and get the values of multiple groups of & 1 and & 2 respectively, and then we can get the average value. By calculating these values produced thereof , we can have the correlation between light loss A and sliding distance !…”
Section: Fiber Loss Monitoring and Statistics Analysismentioning
confidence: 99%